SERIAL PERIPHERAL INTERFACE (SPI) COMMUNICATION APPLICATION AS OUTPUT PIN EXPANSION IN ARDUINO UNO - Baskoro, Farid; Rohman, Miftahur; Nurdiansyah, Aristyawan Putra (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2020)
Serial Peripheral Interface (SPI) is a synchronous serial communication whose data or signal transmission involves Chip Select (CS) or Slave Select (SS) pins, Serial Clock (SCK), Master Out Slave In (MOSI), and Master In Slave Out (MISO). In the Arduino Uno, there are four pins that allow Arduino Uno to perform SPI communication. In this research, SPI communication is implemented to expand the output of the Arduino Uno by using the features of the MCP23S17 IC so that the Arduino Uno, which initially has 20 output pins, can expand to 36 output pins.The results of the research show that the Arduino Uno manages to control 36 output pins. 16 output pins from the MCP23S17, 16 output pins from the Arduino Uno, and 4 pins are used for the SPI communication line. The results of this study also show the form of the SPI communication signal from Arduino Uno in declaring 21 registers on MCP23S17, declaring the MCP23S17 pin register as output, and implementing the output using LEDs.